Optimization of Oil Production by Gas Lift Macaroni in “X” Field - Chrismon Chrismon; R.S. Trijana Kartoatmodjo; Dwi Atty Mardiana (Penerbitan Universitas Trisakti, 2018)
The background of this research was that in X Field many gas wells have stopped flowing years ago and not economical production anymore. Therefore the company has decided to use gas lift which is proper to the sandy oil reservoir characteristic. The tubing of the well has no gas lift mandrel completion as the well was a gas producer. The objectives of this research was that to design gas lift macaroni (GLM) to optimize oil production rate. The design of this research was that the new slim tubing 1.315 inch, called as macaroni tubing, was installed inside the existing 3. 5inch tubing. The gas lift valves are installed inside macaroni tubing. The data collection consists of reservoir data, surface data, and well diagram.The result of this research was that the gas lift macaroni installation can generate oil production rate of 425 STB/day of the three wells. Gas lift valves of well A is four valves, well B is five valves, and well C is three valves. The deviation of software and manual calculation of valves depth is less than 1%. The cost saving by installing gas lift macaroni instead of workover operation to change the existing tubing with new tubing equipped with gas lift valves is USD 5,620,955 of three wells.